(untitled) (Journal of Human Sciences, 2024)
Students today enjoy watching short films on YouTube using their mobile phones and other devices. Consequently, English teachers can guide their students in utilizing these technological tools to enhance their understanding of drama. Current learners are digital natives, familiar with technology, which highlights the importance for English teachers to integrate visual aids into their teaching strategies, especially when teaching English as a foreign language. Teachers should focus on key literary techniques, such as figures of speech, style and context, and narrative structure, to enhance students’ analytical skills. Exploring character development and relationships, as well as encouraging the identification of themes and symbols, further deepens students’ comprehension. By emphasizing these areas, educators can cultivate a richer understanding of literature. Many students feel overwhelmed by the linguistic complexity of literary texts. However, they have the opportunity to appreciate film adaptations of well-known dramas in English. An effective way to understand and value literary texts is through careful analysis of their language and components. Language teachers should help students recognize how the text functions and the specific meanings it conveys. One approach is to select a passage from a drama and pair it with a corresponding film clip. For instance, an extract from Arthur Miller’s *Death of a Salesman* can be used in this way. The findings of the study indicated that the majority of students believe that viewing the film enhances their understanding of the drama. They also found the drama/film (D/F) technique particularly helpful, as it improves both their linguistic and metalinguistic skills, preparing them to better comprehend the visual elements on screen.